Garis panduan perancangan bandar berdaya tahan bencana (disaster resilient cities) di Malaysia - Asmawi, M. Zainora; Ibrahim, Illyani; Yahya, Mohamad Zaki; Ujang, Kamaruzaman; Mohamed, Mohd Zin; Nordin, Zaini; Razak, Kamarrul Azahari (Kementerian Kesejahteraan Bandar, Perumahan dan Kerajaan Tempatan, 2018)
The policy paper addresses the formulation of environmental disaster resilient index for several selected cities in Malaysia. The nation presently highly emphasizes the need for having an appropriate management system for disaster risk strategies in its 11th year Plan (2016-2020). This is parallel with the aspiration of Sendai Framework for Disaster Risk Reduction (2015-2030), that gives signal to the global reduction in the events of disasters by 2030. In this regards, this paper highlights the analysis of Climate Disaster Resilient Index (CDRI) for environmental components in relation to to the environmental related issues: coastal erosion, landslide, sea level rise, and flash flood. The result for CDRI was obtained via conducting a FGD with relevant technical agencies. The mapping of CDRI indicates the level of resilence in the context of environmental condition.